Fighting plagiarism and IPR violation: why is it so important? - Kulathuramaiyer, Narayanan; Maurer, Hermann (Learned Publishing, 2007)
Plagiarism and intellectual property rights (IPR) violations have become a serious concern for many institutions and organizations. The revolutionary development of the Web presents numerous opportunities for such infringements to become even more widespread. This situation creates the risk of introducing a ‘culture of mediocrity’. This paper discusses these issues and proposes means of addressing the concerns by applying viable technological solutions.